A multi-proxy approach to Late Holocene fluctuations of Tungnahryggsjökull glaciers in the Tröllaskagi peninsula (northern Iceland) - Fernández Fernández, José María; Palacios Estremera, David; De Andrés de Pablo, Nuria; Schimmelpfennig, Irene; Brynjólfsson, Skafti; García Sancho, Leopoldo; Zamorano, José J.; Heiðmarsson, Starri; Sæmundsson, Þorsteinn; Team, ASTER (Science of The Total Environment, 2019)
The Tröllaskagi Peninsula in northern Iceland hosts more than a hundred small glaciers that have left a rich terrestrial record of Holocene climatic fluctuations in their forelands. Traditionally, it has been assumed that most of the Tröllaskagi glaciers reached their Late Holocene maximum extent during the Little Ice Age (LIA). However, there is evidence of slightly more advanced pre-LIA positions. LIA moraines from Iceland have been primary dated mostly through lichenometric dating, but the limitations of this technique do not allow dating of glacial advances prior to the 18th or 19th centuries. The application of 36Cl Cosmic-Ray Exposure (CRE) dating to Tungnahryggsjökull moraine sequences in Vesturdalur and Austurdalur (central Tröllaskagi) has revealed a number of pre-LIA glacial advances at ~400 and ~700 CE, and a number of LIA advances in the 15th and 17th centuries, the earliest LIA advances dated so far in Tröllaskagi. This technique hence shows that the LIA chronology in Tröllaskagi agrees with that of other European areas such as the Alps or the Mediterranean mountains. The combined use of lichenometric dating, aerial photographs, satellite images and fieldwork shows that the regional colonization lag of the commonly used lichen species Rhizocarpon geographicum is longer than previously assumed. For exploratory purposes, an alternative lichen species (Porpidia soredizodes) has been tested for lichenometric dating, estimating a tentative growth rate of 0.737 mm yr−1. Ministerio de Economía y Competitivdad (España) Nils Mobility Program Ministerio de Educación, Cultura y Deporte AM Depto. de Geografía Depto. de Farmacología, Farmacognosia y Botánica Fac. de Geografía e Historia TRUE pub